Internal Jugular Venous Pseudoaneurysm in a Patient with Heart Failure and Severe Tricuspid Regurgitation. (31st May 2017) - Phookan, Sujoy; Strickland, Patrick T.; Hanna, Bishoy; Hartlage, Gregory R.; Parikh, Ankit; Clements, Stephen D.
Abstract : The differential diagnosis of a lateral neck mass includes a number of possible etiologies. While jugular venous aneurysms and pseudoaneurysms are rare entities, they should be considered in the differential diagnosis of a pulsatile lateral neck mass. We present a case of an idiopathic jugular venous pseudoaneurysm and its association with worsening tricuspid regurgitation in a patient with heart failure with preserved ejection fraction.